A European theological pentecostal perspective to bivocational ministry. Issue 2 (2nd July 2020) - Samushonga, Hartness M.
ABSTRACT: The practice where ordained ministers carryout their vocation role alongside another non-ministry oriented vocation is common in many church traditions today. Much of the existing dialogue and literature on the subject of bivocational ministry stems from the perspective of the Church of England and American Baptist churches. In this paper, the author adds to the conversation offer some insights on contemporary Pentecostal perspectives from a European context by drawing from the findings of an empirical survey involving European Pentecostals scholars. The essay sheds light on the label of bivocational ministry, its biblical and theological basis, and practices in the context of the European Pentecostal Theological Association.